Wirt-Gast-Komplexe von [bfu.bfu.bfu]: Vorhersage von Ionenselektivitäten mittels quantenchemischer Rechnungen XIII - Palmer, Ursula; Puchta, Ralph (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2020)
The CH2-O-C2H4-O-CH2 moieties in Lehn's cryptand [2.2.2] have been substituted by 2,2′-bifurane groups to get the cryptand [bfu.bfu.bfu]. The ion selectivity of this new cryptandwas investigated by DFT calculations (RB3LYP/LANL2DZp, RB3LYP/LACVP∗, RBP86/LANL2DZp and RBP86/LACVP∗) based on model equations and analysis of the [M ⊂ bfu.bfu.bfu]n+ cryptate structures. The cryptand [bfu.bfu.bfu] is best suited for the alkali cations Na+ and K+, and the alkaline earth cation Sr2+ followed by Ca2+. The cavity of [bfu.bfu.bfu] is thus similar to that in [phen.phen.phen] or [bpy.bpy.bpy]. The selectivity of [bfu.bfu.bfu] is due to the flexibility of the OCCO und CN·NC dihedral angles. The results are independent of the selected DFT methods.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Cryptates; DFT calculations; Selectivity of ion complexation; Supramolecular chemistry